Anaesthesia considerations for the HIV positive parturient (2009)
The HIV epidemic in children parallels that among women on account of perinatal transmission. A combination of antiretroviral therapy and elective caesarean section reduces the rate of vertical transmission to <2%. Elective caesarean section independent of antiretroviral therapy decreases the risk of HIV vertical transmission from mother to baby. However, a caesarean section is a major surgical intervention that has well-reported complications. Women infected with HIV have been reported to be more susceptible to such complications. The multi-organ nature of HIV poses challenges at the time of surgery and anesthesia. Preoperative evaluation will allow a good prediction for the perioperative risk of the HIV-patient. The anesthesiologist should be aware of the possible toxic side effects or the possible interaction of antiretroviral drugs with the anesthetics. Some of these adverse effects may mimic signs and symptoms of the HIV disease itself. Regional anesthesia has been shown to be associated with reduced morbidity and mortality in a wide range of patients, including HIV positive parturients. Finally, the possibility of transmission in the health care setting highlights the need for anesthetists to enforce rigorous infection control policies to protect themselves, other health workers and their patients.